Stimulation of recombination between homologous sequences on plasmid DNA and chromosomal DNA in Escherichia coli by N-acetoxy-2-acetylaminofluorene. - Luisi-DeLuca, C (Proc Natl Acad Sci U S A, 1984)
A plasmid containing a wild-type lac operon and a tetracycline-resistance gene was covalently modified by N-acetoxy-2-acetylaminofluorene and used to transform two series of Lac- Escherichia coli cell types. Each set contained wild-type and repair-deficient mutants. One set of cells contained a lacY mutation and the other a deletion of the entire lac operon. Survival and mutagenesis of the plasmid were measured as a function of the N-acetoxy-2-acetylaminofluorene concentration. The results indicate that when no homologous sequences are present in the chromosomal DNA, mutations occur at a low frequency: at 10% survival the frequency was 1-2 X 10(-4) mutants per transformant. When homologous sequences, the lacY allele, are present in the chromosomal DNA, Lac- plasmids are found at a high frequency in a recA-dependent, lexA-independent fashion: at 10% survival the frequency was 5-10 X 10(-2) mutants per transformant. Southern blot analysis of the restriction enzyme profiles of the resulting plasmid and host-cell DNA sequences showed recombinational transfer of host sequences to the N-acetoxy-2-acetylamino-fluorene-treated plasmid had occurred. When the host chromosomes contained Lac+ homologous sequences no mutants were found, indicating that the results were not caused by error-prone recombination. IMAGES: